(untitled) (Al-Academy, 2016)
The research is dedicated to study technical and dramatic recruitment of the clown character in Child’s Theater Shows This research consist of four chapters ; first chapter is dealing with the problem of the research which defined by the following question :" Does the educational and dramatic recruitment of the clown character achieved in Child’s Theater Shows?"The research is summarized in sets of points such as :•Make use of this research for the benefit of employees in the child’s theater , especially directors, actors, technicians, workers and dress designers .•To benefit concerned educational institutions in the field of child’s theater ; such as : child’s culture house , theater & cinema office which are belonging to the education ministry and technical organizations in the field of child’s arts . Accordingly the present research is aimed at the following: •Reveal of educational recruitment of clown character in the shows of child’s theater . The chapter defines the limitation of the research which is concerned objectively in the shows of the play performed in child’s theater , which contains the clown character in Baghdad ,from the period of ( 2000 – 2010 ) . this chapter also included defining some terms and their definitions .Second chapter is defined to the theoretical framework of the research and to look for previous studies with discussions . This chapter includes three categories ; the first is dealing with child’s theater , second category deals with the concept of clown and the art of clowning , third category deals with the clown in child’s theater , the chapter is concluded with the most indicators resulted from theoretical framework and present the previous studies with discussion.Third chapter deals with the methodology of the research and researcher’s procedures and defining society of the research which includes ( 20) theater shows that take the clown character as a hero or subordinate character . The researcher chooses the sample of his research randomly by writing the names of shows on cuttings of papers each round separately ,that the sample becomes ( 5 ) theater shows: And to achieve the aim of the research, the researcher carried out his research tool represented by ( form of analyzing the educational and the drama functions of the clown character) and subjected to a number of experts to identify their validity and to measure the two research aims set for it. Also measuring the stability and Holistic equation was used to find the accord coefficient between the arbitrators(the analyzers). As for the forth chapter which was assigned for the most important results , the researcher has reached in light with the results amongst them :-1- All the shows presented in the child’s theatre, which handling the clown character as a main or secondary character , did not use the high performance skill, but depending on only the utterance.2-Most of representatives of the clown character in the child theater depended in their performance on their accumulated individual experiences and they did not acquainted with the rules of the clown character and its basic elements. According to the conclusions, the researcher has reached, he recommended the following:-1-Introducing educational approach about the clowning art in the material of the child theatre.2- Delegation those concerned with the child theatre especially those specialized in the clowning art and made them participated in global training sessions for improving their capabilities. Thus the researcher has suggested performing the following studies: The artistic and educational mobilizing for the clown character in the TV. Programs directed for the child